Three Critical Characteristics of Leadership: Character, Stewardship, Experience. (December 2014) - Gini, Al; Green, Ronald M.
Abstract There is no one definition of leadership. The leadership equation is never set or fixed. Time, place, specific problems, the particular parties involved all play a role in the leadership equation. Nor is there one specific list of attributes, virtues, or skills that all leaders must and do possess. Nonetheless, we argue that at its core, all forms of ethical leadership are based on three elemental ingredients: character, stewardship, and experience.